2009
DOI: 10.1038/ni.1719
|View full text |Cite
|
Sign up to set email alerts
|

Divergent functions for airway epithelial matrix metalloproteinase 7 and retinoic acid in experimental asthma

Abstract: The innate immune response of airway epithelial cells to aeroallergen initiates the development of T cell responses that are central to allergic inflammation. Although proteinase allergens induce the expression of interleukin 25 we show that epithelial matrix metalloproteinase 7 (MMP7) was expressed in asthma and was required for maximal activity of IL-25 in promoting T helper type 2 cell differentiation. Allergen-challenged Mmp7−/− mice showed reduced airway hyperreactivity, allergic inflammatory cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
102
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(104 citation statements)
references
References 50 publications
2
102
0
Order By: Relevance
“…Matrilysin/matrix metalloproteinase (MMP) 7 is an epithelial MMP that is induced in response to injury, infection, or allergen challenge (6)(7)(8). We reported that, in response to lung or colon injury, transepithelial migration of neutrophils is halted in Mmp7 2/2 mice (9, 10).…”
mentioning
confidence: 99%
“…Matrilysin/matrix metalloproteinase (MMP) 7 is an epithelial MMP that is induced in response to injury, infection, or allergen challenge (6)(7)(8). We reported that, in response to lung or colon injury, transepithelial migration of neutrophils is halted in Mmp7 2/2 mice (9, 10).…”
mentioning
confidence: 99%
“…In complete Aspergillus allergen-immunized mice model, epithelial metalloproteinase 7 (MMP7) activated IL-25 to promote Th2 cells differentiation, but inhibited RALDH1 and thus Treg development (61). Therefore, MMP7 Ϫ/Ϫ mice showed higher RALDH1 expression, lower IL-4 and IL-5 in bronchoalveolar fluid, and dampened airway hyperreactivity.…”
Section: Ra Regulates Allergy Through Tregsmentioning
confidence: 99%
“…29 Recently it has been shown that RALDH-1, the ratelimiting enzyme that converts retinaldehyde to RA, was up-regulated in response to allergic stimulation in the airway epithelium, which indicates a possible site for RA production in the lung. 60 Further, liposome-mediated delivery of RA 1 hour before immunization resulted in attenuated lung inflammation compared with control mice that received empty liposomes. Similarly, Citral, an inhibitor of RALDH-1, resulted in reduced synthesis of RA and fewer Tregs in the lung.…”
Section: Tregs In Allergic Inflammationmentioning
confidence: 99%